See the investment forest and the trees - Kahn, Michael N. (FTPress Delivers elements, 2010)
"This Element is an excerpt from Technical analysis plain and simple: charting the markets in your Language (ISBN: 9780137042012) by Michael N. Kahn. Stop burying yourself in data: Cut to the chase and get the insights you need to discover real market trends and make better trades!"--Resource description page.